Penerapan Asas Non Retroaktif Terhadap Pertanggungjawaban Tenaga Medis Pelaku Aborsi (Studi Putusan Nomor 36/Pid.Sus/2024/Pn Dps) - Aprilyani Ikra, Putri; Sunariyo, Sunariyo; Elviandri, Elviandri (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
Abortion is the process of forcibly terminating a pregnancy with deliberate intent to end the life of the fetus. This research aims to analyze the legal aspects of criminal abortion conducted by medical professionals, focusing on the verdict of the District Court of Denpasar Number 36/Pid.Sus/2024/PN Dps. The research methodology used is a normative approach, involving literature review and analysis of relevant laws and court decisions. The findings indicate that criminal abortion by medical professionals can be analyzed from various perspectives. The ruling of the District Court of Denpasar serves as a foundation for understanding the application of law in abortion cases involving medical professionals in Indonesia.The conclusion of this research highlights the complexity in legal handling of abortions, especially when medical professionals are involved. The implications of this research can contribute to formulating more appropriate legal policies in handling abortion cases in Indonesia, taking into account medical, ethical, and justice aspects in law enforcement.